Comparison between South Korean and Singaporean project management approach in construction - Foo, Steven Tek Shyong. (2008)
The purpose of this dissertation is to examine the practice and methods used for project management in the Singapore Construction Industry. South Korean Construction Companies have been very active in the Middle East, Europe and Asia, especially in Singapore. A study has been made to identify their long established management system, their strengths and weaknesses so as to understand how and why their construction management system is so well established in domestic as well as overseas markets.